1974
DOI: 10.1007/bf01221637
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid pattern of adipose tissue and liver triglycerides according to fat droplet size in liver parenchymal cells of diabetic subjects

Abstract: 111 40 diabetic inpatients the fatty acid pattern of triglycerides in liver Iat and in subcutaneous adipose tissue was determined by gas liquid chromatography. With rising size oI fat droplets in liver parenehyreal cells there was a significant increase of palmitic acid (C:16), oleic acid (C 18: 1) and linoleie acid (C 18:2) as well as a decrease of myristoleic acid (C 14 : 1), araehidonic (C 20:4) and eieosapentaenoie acid (C 20:5) in liver tri-glyeerides, resulting in a fatty acid composition in big droplets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The fatty acid distribution in the triglyceride fractions differed significantly from that in the fatty acid fractions. The predominance of unsaturated fatty acids in the triglycerides is consistent with earlier observations (14)(15)(16)(17). In contrast, saturated fatty acids predominated in the free fatty acid fractions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The fatty acid distribution in the triglyceride fractions differed significantly from that in the fatty acid fractions. The predominance of unsaturated fatty acids in the triglycerides is consistent with earlier observations (14)(15)(16)(17). In contrast, saturated fatty acids predominated in the free fatty acid fractions.…”
Section: Discussionsupporting
confidence: 92%
“…Laurel1 and Lundquist found up to 1.7% pentadecanoic acid in hepatic triglycerides and no heptadecanoic acid (14). Neither Kessler et al (15), Takahashi and Tanaka (16), or Singer et al (17) reported any odd chain fatty acids in the liver. Any presence of pentadecanoic acid in the free fatty acid fraction would have resulted in an underestimation of the free fatty acid concentration in our study.…”
Section: Lipid Analysismentioning
confidence: 93%
“…Stepping through discrete values for ndb 1 shows that ndb 1 should be in the range ± 1 in order for ndb to remain in a valid range; it is not possible to determine a precise value for ndb 1 from the data in this study. A propensity for a negative value is supported by Singer et al and Mavrelis et al, which indicate that liver fat is more saturated at higher PDFF levels and, on this basis, the present study hypothesizes a value at the low end of the valid range of ndb 1 = −1.…”
Section: Resultssupporting
confidence: 78%
“…In addition to optimizing for the average ndb, there may be compositional changes in the fat compartment that cause ndb to systematically vary with PDFF. Changes in free fatty acid concentration and triglyceride composition with fat content have been reported in chemical analyses of biopsy samples, and there have been suggestive findings in MRS of correlation (both positive and negative) between ndb and the volume of fat in various depots, although not specifically in liver . In order to accommodate a systematic variation of this type, ndb was modeled as a constant plus linear term in PDFF: ndb=ndb0+ndb1·.2emPDFF …”
Section: Methodsmentioning
confidence: 99%
“…Our results tally with other reports on human hepatic tissue that employed chromatography and other analytical in vitro methods. As far back as 50 years ago, Singer [ 24 ] showed that mono-, di- and polyunsaturated fatty acid content differs between normal and steatotic livers and that polyunsaturated fatty acid (PUFA) content decreases in correlation with increased diameter of fat droplets.…”
Section: Discussionmentioning
confidence: 99%